(untitled) - Grobben, Gert (Netherlands, 1998)
The influence of physiological factors and the medium composition on the growth, EPS production and the sugar composition of the EPS produced by Lactobacillus delbrueckii subsp. bulgaricus NCFB 2772 is studied in detail.
Keywords: Lactobacillus,Khuẩn Lactobacillus